ESL Educators’ Belief in Teaching English for Academic Purposes (EAP) to Low Level Learners - Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Suriya Kumar, Sinnadurai; Zarina, Mohd Ali; Zuraina, Ali (Universiti Malaysia Pahang, 2015)
English for Academic Purposes (EAP) emerged from the broad concept of Communicative Language Teaching (CLT). EAP is intended to facilitate learners in academic setting whilst the latter is more general in its purpose and approach. As such, lack of fundamental knowledge and understanding among ESL educators on the differences of the two teachings could lead to ineffective EAP classroom practices. This study identifies 72 ESL educators’ belief on EAP teaching for low level engineering undergraduates at four Malaysian technical universities. The study used an online reflective questionnaire adapted from Alexander (2012) and semi structured interviews with eight senior members of the institutions. The findings indicated a tension which might exist between the beliefs about general CLT and specific EAP teaching among the educators. The lack of awareness among the educators on the differences between the two has consequences on their EAP practices. The senior educators concurred with the findings and highlighted the need of specific EAP competency and formal trainings for the ESL educators in teaching EAP at the Malaysian technical and engineering based higher education institutions